2014
DOI: 10.1002/ejp.528
|View full text |Cite
|
Sign up to set email alerts
|

Oral 2‐hydroxyoleic acid inhibits reflex hypersensitivity and open–field‐induced anxiety after spared nerve injury

Abstract: Oral administration of the modified omega 9 fatty acid, 2-OHOA, mediates antinociception and prevents open-field-induced anxiety in the SNI model in Wistar rats, which is mediated by an inhibition of spinal dorsal horn microglia activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 69 publications
1
12
0
2
Order By: Relevance
“…In our previous work with the SCI model [2], no evidence for the development of anxiety measured with the open field test was observed, in line with another study [8]. In contrast the present study with the "spared nerve injury" model supports our previous observation that anxiety develops after peripheral nerve injury [18], suggesting the involvement of pathology-specific mechanisms that are more closely related to this comorbidity. In a previous study we suggested that the neural mechanisms that mediate apprehension are independent of those that mediate aversion measured with the PEAP test [2].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In our previous work with the SCI model [2], no evidence for the development of anxiety measured with the open field test was observed, in line with another study [8]. In contrast the present study with the "spared nerve injury" model supports our previous observation that anxiety develops after peripheral nerve injury [18], suggesting the involvement of pathology-specific mechanisms that are more closely related to this comorbidity. In a previous study we suggested that the neural mechanisms that mediate apprehension are independent of those that mediate aversion measured with the PEAP test [2].…”
Section: Discussionsupporting
confidence: 79%
“…The rats were recorded and tracked for five minutes, and the software calculated the total time spent in each zone and the total distance moved. Anxiety behavior was confirmed when the animals demonstrated reduced exploration time within the inner zone also on day 21 after SNI [18,19].…”
Section: Methodsmentioning
confidence: 85%
See 1 more Smart Citation
“…Behavioural alterations have been described in rat models of peripheral traumatic nerve injury (Hu et al., 2007; Blackbeard et al., 2012; Galan‐Arriero et al., 2015; Wang et al., 2015; Avila‐Martin et al., 2015; Grégoire et al., 2012), neuropathic viral infection (Hasnie et al., 2007; Wallace et al., 2007a) and drug‐induced neuropathies (Wallace et al., 2007b; Huang et al., 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Mechanical reflex hypersensitivity (Avila-Martin et al, 2015) was recorded at specific time-points after SCI by two independent examiners blinded to the experimental conditions. The rats were placed in a plastic box that was placed on a wire mesh platform.…”
Section: Behavioral Testsmentioning
confidence: 99%